2022
DOI: 10.1001/jamacardio.2021.4996
|View full text |Cite
|
Sign up to set email alerts
|

Association of Differences in Treatment Intensification, Missed Visits, and Scheduled Follow-up Interval With Racial or Ethnic Disparities in Blood Pressure Control

Abstract: IMPORTANCE Black patients with hypertension often have the lowest rates of blood pressure (BP) control in clinical settings. It is unknown to what extent variation in health care processes explains this disparity.OBJECTIVE To assess whether and to what extent treatment intensification, scheduled follow-up interval, and missed visits are associated with racial and ethnic disparities in BP control. DESIGN, SETTING, AND PARTICIPANTSIn this cohort study, nested logistic regression models were used to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 46 publications
(83 reference statements)
2
25
0
2
Order By: Relevance
“…Indeed, social determinants of health are recognized as important drivers of hypertension control. 42 However, from the perspective of strength of impact and feasibility of measurement, these were deferred with consideration for possible inclusion in further iterations of this model. Also, population-based hypertension screening is an important determinant of BP control at the population level.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, social determinants of health are recognized as important drivers of hypertension control. 42 However, from the perspective of strength of impact and feasibility of measurement, these were deferred with consideration for possible inclusion in further iterations of this model. Also, population-based hypertension screening is an important determinant of BP control at the population level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, low-income low-wage workers may be employed at multiple jobs without the ability to take time off for a healthcare visit; patients who rely on public transit or reside in rural areas may spend hours commuting to and from an office visit. These barriers result in fewer clinical visits and therefore fewer blood pressure measurements and opportunities to identify uncontrolled hypertension [ 57 , 58 ]; missed visits can result in disparities in hypertension outcomes [ 20 ]. SMBP monitoring facilitates equity through earlier identification of uncontrolled hypertension and provides more opportunities for clinicians to intensify medications in response to uncontrolled blood pressure values.…”
Section: How Smbp Monitoring Could Address Equity In Hypertension Con...mentioning
confidence: 99%
“…They can be made better or worse by the way we deliver care. Healthcare process factors that are controlled or influenced by the health system, such as infrequent follow-up and suboptimal prescribing of medication treatment for hypertension, are major barriers to achieving BP control [20][21][22]. For example, health systems that have implemented team-based care where non-physician team members can make treatment decisions, standardized treatment algorithms, and frequent follow-up have achieved improved BP control across their patient population regardless of race or income [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Primary care clinics may not be open at times that are convenient for patients who do not have flexible work hours or demanding caregiving responsibilities. 3,5 They may also require making appointments far in advance before patients know their schedules or availability. In addition, many Americans remain uninsured or underinsured, and those individuals are less likely to receive care or have controlled blood pressure.…”
Section: See Article By Luomentioning
confidence: 99%
“…A recent study in a safety-net county-based health system found that missed visits and treatment intensification accounted for 14% and 21% of the higher probability of uncontrolled hypertension seen in Black patients compared with other race and ethnic groups. 3 Thus, barriers to accessing regular care may uniquely contribute to the racial and socioeconomic inequities seen in blood pressure control.…”
mentioning
confidence: 99%